Patterns of changes in immune and hormonal regulation in hand-arm vibration syndrome and sensorineural hearing loss - G. M. Bodienkova; S. I. Kurchevenko (Бюллетень сибирской медицины, 2020)
The purpose of the research was to identify changes in immune and hormonal regulation in patients with hand-arm vibration syndrome and sensorineural hearing loss to substantiate informative biomarkers.Materials and methods. Men with occupational injury induced by exposure to vibration and noise were examined. The first group included 26 people diagnosed with stage 1 and 2 hand-arm vibration syndrome. The second group consisted of 38 patients diagnosed with sensorineural hearing loss. Serum levels of cortisol, dehydroepiandrosterone sulfate, prolactin, free triiodothyronine (T3), free thyroxine  (T4), thyroid-stimulating hormone (TSH), and interleukins IL-1β, IL-8, IL-10 were determined by enzyme-linked immunosorbent assay.Results. The results of the study revealed the peculiarities in the immune and hormonal regulation in hand-arm vibration syndrome and sensorineural hearing loss. More pronounced changes were observed in sensorineural hearing loss. A common pattern in patients with hand-arm vibration syndrome and sensorineural hearing loss was an increase in cortisol, prolactin and IL-8 and a decrease in free T4 and IL-1β. Differences in the identified changes in the immune and hormonal status were characterized by increased TSH production in the first group, and increased free T 3 production and decreased IL-10 in the second group. In hand-arm vibration syndrome, high levels of cortisol were accompanied by a decrease in the IL-1β and IL-10 concentrations. In sensorineural hearing loss, an increase in the prolactin concentration was accompanied by increased production of IL-8.Conclusions. The identified features of immune and hormonal relations may be induced by the intensity of cortisol and prolactin production under the effects of various physical factors. Persistent high levels of cortisol and prolactin in the examined patients are important pathogenetically significant factors in the development of the disease. New laboratory indicators (IL-4, prolactin, free T3) for additional diagnosis of occupational sensorineural hearing loss were identified.